Piezoelectric bimorph-based shear force microscopy for the construction of noble metal plasmonic structures in air. (1st July 2015) - Cai, Wei; Yang, Mu; Wang, Yingjie; Shang, Guangyi
Abstract: In this article, we present an alternative method to directly manipulate the noble metal structures in air. The method is carried out based on a home-made shear force microscope, which mainly consists of a fiber probe-bimorph beam shear force sensor, a scanning probe microscope controller, and a nano-positioning stage. The magnitude of the probe-sample interaction forces as a function of the set-point ratio is estimated, which shows that the magnitude of the forces is inversely proportional to the set-point ratio. The microscopic imaging and manipulation can be realized at the higher and lower set-point values, respectively. Typical results of imaging at the set-point ratio of larger than 90% and manipulation at that of lower than 60% are demonstrated. The results suggest that this method would provide a promising way to study the relation between plasmonic structures and optical properties on the micro/nano scale.